Cytotoxic impact of a perillyl alcohol–temozolomide conjugate, NEO212, on cutaneous T-cell lymphoma in vitro. (December 2019) - Silva-Hirschberg, Catalina; Hartman, Hannah; Stack, Samantha; Swenson, Steve; Minea, Radu O.; Davitz, Michael A.; Chen, Thomas C.; Schönthal, Axel H.
Background: Mycosis fungoides (MF) and Sézary syndrome (SS) are subtypes of primary cutaneous lymphomas and represent complex diseases regarding their physiopathology and management. Depending on the stage of the disease, different treatment regimens are applied, but there is no consensus on an optimal approach. Prognosis for patients with early stage MF is favorable, but significantly worsens in advanced disease and in SS, where patients frequently relapse and require multiple therapies. Methods: We investigated the potential anticancer effects of NEO212, a novel compound generated by covalently conjugating perillyl alcohol (a natural monoterpene) to temozolomide (an alkylating agent), on MF and SS cell lines in vitro . HUT-78, HUT-102, and MyLa cells were treated with NEO212 under different conditions, and drug effects on proliferation, viability, and apoptosis were characterized. Results: NEO212 inhibited proliferation, diminished viability, and stimulated apoptosis in all cell lines, although with varying degrees of potency in the different cell lines. It down-regulated c-myc and cyclin D1 proteins, which are required for cell proliferation, but triggered endoplasmic reticulum stress and activation of caspases. Pretreatment of cells with antioxidants ascorbic acid and beta-mercaptoethanol prevented these NEO212-induced effects. Conclusions: NEO212 exerted promising anticancer effects on SS and MF cell lines. The generation of reactive oxygen species (ROS) appears to play a key role in the NEO212-induced cell death process, because the blockage of ROS with antioxidants prevented caspase activation. We propose that NEO212 should be investigated further toward clinical testing in these tumor types.